Successful transfemoral antegrade valve-in-valve implantation of a SAPIEN XT valve into a degenerated mitral valve prosthesis - Bekeredjian, Raffi; Chorianopoulos, Emmanuel; Katus, Hugo (The journal of invasive cardiology, 2012)
Transfemoral aortic valve implantation has become an important interventional technique for patients with severe aortic stenosis and high surgical risks. The mitral valve has been a much greater challenge for interventional procedures, and no percutaneous mitral valve implantation system has yet been developed and approved. Here, we report the successful transfemoral, antegrade, valve-in-valve implantation of the SAPIEN XT valve (Edwards Lifesciences) into a degenerated mitral valve bioprosthesis. The patient was an 81-year-old woman with severe regurgitation of her 27 mm Epic mitral valve prosthesis (St. Jude Medical), suffering from dyspnea on mild exertion with a calculated logistic EuroScore of 48% and an Society of Thoracic Surgeons score of 29%. Thus, another surgical mitral valve replacement was refused by the patient and was considered as extremely high risk by the cardiac surgeon. Therefore, a transfemoral valve-in-valve implantation was planned. The femoral vein was used as an access site, followed by a transseptal puncture and placement of a super-stiff wire into the left ventricle. Then, the septum was dilated and a 26 mm SAPIEN XT valve was inserted through the septum and then inserted into the mitral valve prosthesis. Under rapid pacing, a very slow inflation of the balloon was performed, leading to a stable valve-in-valve implantation without any regurgitation. The patient was transferred to a normal ward after 2 days. This procedure is an off-label, technically very challenging, high-risk implantation that could be attempted in very select patients after discussion by a heart team and by experienced implanters.
DOI nicht vorhanden